-2(x+9)+3(2x-3)=-32

Simple and best practice solution for -2(x+9)+3(2x-3)=-32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+9)+3(2x-3)=-32 equation:


-2(x+9)+3(2x-3)=-32

We simplify the equation to the form, which is simple to understand
-2(x+9)+3(2x-3)=-32

Reorder the terms in parentheses
+(-2x-18)+3*(2x-3)=-32

Remove unnecessary parentheses
-2x-18+3+*(+2x-3+)=-32

Reorder the terms in parentheses
-2x-18+(+6x-9)=-32

Remove unnecessary parentheses
-2x-18+6x-9=-32

We move all terms containing x to the left and all other terms to the right.
-2x+6x=-32+18+9

We simplify left and right side of the equation.
+4x=-5

We divide both sides of the equation by 4 to get x.
x=-1.25

See similar equations:

| 9t-10=6t | | x^2(x^2-5)-2x(x^2-4)+4=0 | | 6x^4-8x^3+10x= | | 3y-9=6+3 | | (3*-2*1)+2= | | 11x+x+3=4(x-2)+8x+11 | | 9x-2=2x | | 3y-9=0+3 | | 3m=5.7 | | .4x-9=.1(x+30) | | -1=u-2 | | 52=-2(22-x)+4(x-3) | | 32x^2+18=0 | | (a+1)*(a-3)x=(a+1)*(a+4) | | .8(220-a)=120 | | 2(1+v)=-6+4v | | 117+7y=180 | | 9x^2-18xy-8x+16y=0 | | 15n-6n= | | 3s+s=-49 | | -9.8(27x-65)=78.24(6x+34) | | 4(x-5)-2(x+2)=-22 | | 3e-4=-2 | | 2+14a=-8+9a | | 7y+18=180 | | 60x^2-20xy+12x=0 | | -7(a-6)=2-2a | | 4(x-3)=2x+2(x-6) | | 2x^6-17x^4+17x^3= | | 15x+45=180 | | ba-4b=c | | .5x+3=2 |

Equations solver categories